ESTIMATES OF CURRENT AND FUTURE DEVELOPMENT OF LABOUR FORCE AND MIGRATION RELATIONS OF RUSSIAN ARCTIC’S REGIONS - A. G. Korovkin; I. N. Dolgova; E. A. Edinak; I. B. Korolev (Модернизация, инновация, развитие)
This article discusses the use of balance of labour resources and population and labour resources movements balance for the assessment of the current and future state of regional labor markets and migration linkages in the regions of the Russian Arctic. The purpose of this article is to obtain projections of the dynamics of the main indicators of balance of labour resources, structure and dynamics of population and labor resources of the Russian Arctic regions. The study was performed in the methodology of balance of labour resources and population and labour resources movements balance. The model of population and labor resources movement, taking into account the repeated displacement of people is used. With account of the historical period we forecast the main parameters of population movements structure. The results of calculations on the example for the regions of the Asian and European parts of the Russian Arctic is given. The main problems of the Arctic regions labor resources are identifi ed. The resulting estimates of prospective changes in the structure of balance of labour resources, the most signifi cant sources of additional labor resources, changes to the importance of these sources. The article considers the trends of inter-regional movement of population and labor resources. The analysis of the main areas of origin and regions of arrival is made. The main donor regions and the recipient regions for regions of the Russian Arctic are named. The analysis of structural imbalances on the regional labour markets is made. The contribution the Arctic regions in the magnitude of structural unemployment is measured. Its shown, which regions can be conventionally considered labor-surplus and-defi cient. The results of the study can be used in the development of regional employment programmes, the development and implementation of migration policy, the development of the forecast of labour resources balance sheet, and especially of the forecast of labour resources balance sheet for the regions of the Russian Arctic. The article presents recommendations for improving tool of analysis and forecasting, measures of state social and economic policy are proposed that will enable more effi cient use of labour resources in the Arctic, can use to solve problems of coordination of labor demand and its supply on regional labour markets more eff ectively.